The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.enpol.2017.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Assessing fairness of dynamic grid tariffs

Abstract: The surge in the supply of intermittent renewable energy creates new challenges for electricity networks. The high variation in the supply either requires costly network extensions or the implementation of incentives that reduce peaks. One variant of the latter are dynamic tariffs. While dynamic pricing provides an efficient tariff scheme, people may perceive it as unfair. This paper examines to which extent such peak pricing is actually unfair and, if so, how this unfairness can be lessened by adapting the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 35 publications
(30 reference statements)
1
36
0
Order By: Relevance
“…These conclusions are in line with the findings in behavioural economics and ethics literature (Neuteleers et al, 2016). Behavioural economics teaches us that people react negatively to price changes which are not based on changes in costs but on, in their view, arbitrary conditions, such as scarcity in the market.…”
Section: Figure 3 Assessment Of the Fairness Of Various Types Of Netsupporting
confidence: 78%
See 2 more Smart Citations
“…These conclusions are in line with the findings in behavioural economics and ethics literature (Neuteleers et al, 2016). Behavioural economics teaches us that people react negatively to price changes which are not based on changes in costs but on, in their view, arbitrary conditions, such as scarcity in the market.…”
Section: Figure 3 Assessment Of the Fairness Of Various Types Of Netsupporting
confidence: 78%
“…A survey among a panel of Dutch consumers 29 has shown that, on average, people do not consider dynamic tariffs, which are depending on the congestion in the network, unfair (Neuteleers et al, 2016). The percentage of people considering dynamic tariffs as (very) unfair is about the same as the percentage considering these tariffs as (very) fair (Figure 3).…”
Section: Figure 3 Assessment Of the Fairness Of Various Types Of Netmentioning
confidence: 63%
See 1 more Smart Citation
“…As discussed by Neuteleers et al the concrete tariff implementation plays an important role in setting prices that clearly associates with revenues needed to maintain the grid, in providing predictable prices, and in using clear arguments [48]. In setting such tariffs for the future electricity system, this is likely to result in a complex puzzle.…”
Section: Resultsmentioning
confidence: 99%
“…However other problems could arise such as fairness or cost recovery. Reference [9] studied the fairness of dynamic grid tariffs and pointed that it is important to remember all the principles of tariff design when assessing them.…”
Section: State Of the Art And Contributionmentioning
confidence: 99%